Analysis of Competitiveness and Impact of Government Policies in the Business of Laying Chicken in Sindang Kasih Village West Ranomeeto Sub District South Konawe District Using the Policy Analysis Matrix Approach - Zani, Munirwan (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2022)
This study aims to assess the competitiveness of the laying hens business in Sindang Kasih Village, East Ranomeeto District, South Konawe Regency, as well as the influence of government policies on the laying hens' company. In March 2021, the study was conducted in Sindang Kasih Village, East Ranomeeto District, South Konawe Regency. All of the participants in the study were laying hen breeders. The research sample is five businesses. The type of research data is quantitative, namely information in the form of numbers. Research variables include foreign and domestic input costs, private prices, social prices, production and revenue. Data analysis uses the Policy Analysis Matrix approach. The findings revealed that the laying hens business in Sindang Kasih Village, East Ranomeeto District, South Konawe Regency, had a competitive advantage, based on indicators of competitive advantage such as the Private Cost Ratio (PCR) value of 0.31 and indicators of comparative advantage such as the Domestic Resource Cost Ratio (DRCR) value of 0.25. The influence of government policy on laying hen output in Sindang Kasih Village, East Ranomeeto District, South Konawe Regency, leads the output value at social prices to be higher than the output value at private prices. Meanwhile, the influence of government policy on laying hen inputs leads profits to be higher at private pricing due to input import obstacles, resulting in production using comparatively cheap local inputs. Based on the conclusions of the study, it is necessary to have a government policy regarding increasing the selling price of laying hens products at the farmer level and supporting export activities by increasing the production of laying hens because the research results show that the price of laying hens in the international market is relatively high compared to the prevailing prices at the farmer level. And the production capacity of laying hens has been unable to export or meet international market demand.